2016
DOI: 10.1002/hep.28409
|View full text |Cite
|
Sign up to set email alerts
|

Theranostical nanosystem‐mediated identification of an oncogene and highly effective therapy in hepatocellular carcinoma

Abstract: Because the primary surgical treatment options for hepatocellular carcinoma (HCC)-including hepatic resection and liver transplantation-often fail due to recurrence and metastasis, identifying early prognostic biomarkers and therapeutic targets for HCC is of great importance. This study shows that transducin b-like protein 1-related protein (TBLR1) is a key HCC oncogene that plays important roles in HCC proliferation, antiapoptosis, and angiogenesis by regulating the Wnt/ b-catenin pathway. The folate-targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…Multifunctional delivery systems that carry therapeutic and diagnostic imaging agents with FA are emerging concept for effective targeted therapy. The diagnostic imaging agents contain fluorophores, quantum dots (QDs), 110 small-molecule paramagnetic agents, 111,112 SPIO, [113][114][115][116][117] and so forth. Wang et al 110 designed a smart multifunctional polymeric micelle for targeted therapy of HCC.…”
Section: Vitamin-based Active Targetingmentioning
confidence: 99%
“…Multifunctional delivery systems that carry therapeutic and diagnostic imaging agents with FA are emerging concept for effective targeted therapy. The diagnostic imaging agents contain fluorophores, quantum dots (QDs), 110 small-molecule paramagnetic agents, 111,112 SPIO, [113][114][115][116][117] and so forth. Wang et al 110 designed a smart multifunctional polymeric micelle for targeted therapy of HCC.…”
Section: Vitamin-based Active Targetingmentioning
confidence: 99%
“…TBL1XR1 siRNA#1: 5′-TCT CTA GAT TGG AAT AGT GAAdTdT-3′ (Guo et al 2016) TBL1XR1 siRNA#2: 5′-CGT AAT GCC TGA TGT AGT AdTdT-3′ Negative control siRNA (ncRNA): 5′-TTC TCC GAA CGT GTC ACG TdTdT-3′…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Robust cell proliferative capacity and resistance to anticancer agents are major hurdles to the development of efficient chemotherapy, and abnormal cell proliferation and apoptotic cell death have been extensively studied to identify potential therapeutic targets against human cancer (30). Various cellular components, including hypoxia-inducible factor-1α (31), transducin β-like protein 1-related protein (32) and fibroblast growth factor receptor 4 (33), have been shown to contribute to cancer cell proliferation, and due to their anti-apoptotic properties, they have been studied as putative targets for cancer therapy (31)(32)(33). The results of the present study revealed that CYP2J2 also serves important roles in inducing cell proliferation and inhibiting the cell death induced by anticancer agents.…”
Section: Effect Of Cyp2j2 Overexpression On Resistance To An Anticancmentioning
confidence: 99%